Improving resource choices for students and professionals in accounting and finance according to personality characteristics: Exploratory study - Ghunaimi, Hisham Al; Al Kharusi, Zalkha Ibrahim Ali Said; ALBuwaiqi, Khoula Salim Ali (International Journal of Innovative Research and Scientific Studies, 2025)
This research investigates how personality traits, categorized by the Myers-Briggs Type Indicator (MBTI), influence the choice of learning resources among accounting and finance students and professionals. It evaluates the effects on skill enhancement and educational methodologies in the discipline. A preliminary study was carried out utilizing structured surveys to analyze the connection between personality types and preferred learning methods (such as books and online tools). This study offers initial results that establish a basis for more extensive research in the future. The findings reveal that 70% of participants saw a notable improvement in learning outcomes when their selected resources matched their MBTI personality types. The study highlights the significance of personalized resource selection in boosting understanding, efficiency, and professional advancement. Tailoring learning resources to align with personality traits leads to enhanced educational experiences and career growth. Nonetheless, challenges, including small sample sizes, need to be addressed in subsequent research. This research introduces an innovative framework that connects MBTI personality traits with ideal learning resources, providing practical recommendations for educators, students, and professionals to optimize learning efficacy and productivity in the fields of accounting and finance.